Permutation of fuzzy AHP and AHP methods to prioritizing the alternatives of supply chain performance system - Tyagi, Mohit; Kumar, Pradeep; Kumar, Dinesh (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
The objective of this research was to examine the most preferable alternative to improve the supply chain performance (SCP) of automobile industries, located in the National Capital Region (NCR) of India. To meet out the above objective, a performance based model has been developed by identifying the needful measures. The fuzzy analytic hierarchy process (FAHP) extent’s analysis has been applied to analyze the model in order to evaluate the performance of considered alternatives namely suppliers, 3PLs providers, web-based technologies and advanced manufacturing technologies and to make the findings more robust, the analytic hierarchy process (AHP) approach has been applied using defuzzified inputs, then discussed the comparison of results. The findings suggest that alternative supplier’s is more imperative among the all considered alternatives and plays a critical role in improving the SCP system. Significance: The proposed hierarchy based model has been considered first time to analyze the SCP system of Indian automobile industries located in NCR region. Critical analysis of the entire four alternatives with role and effect has been discussed. The outcomes of this study may deliver a trail to the managers to build a suitable performance measurement (PM) system in order to improve the overall SCP of an organization.